A battery binder and its preparation method and application

By developing a battery binder with block copolymer structure, the problems of high brittleness of the binder and difficult to maintain the integrity of the counter electrode structure in the prior art are solved, and the excellent mechanical properties of the battery pole sheet and the improvement of the battery energy density are achieved.

CN116995233BActive Publication Date: 2025-02-28SHENZHEN YANYI NEW MATERIALS CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202210442379.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-04-25
Publication Date
2025-02-28
Estimated Expiration
2042-04-25

AI Technical Summary

Technical Problem

The binders such as PVDF in existing lithium-ion batteries have high brittleness, difficulty in maintaining the integrity of the electrode structure, and negative impacts on the environment and production process, making it difficult to adapt to the needs of new energy technologies.

Method used

A binder for batteries made of block copolymers composed of block A and block B was developed. Block A was prepared from aromatic diisocyanate and aromatic diamine, and block B was prepared from aliphatic diisocyanate and aliphatic diamine, combining strength and flexibility to improve the bonding strength and flexibility of the binder.

Benefits of technology

This adhesive makes the battery pole plate have excellent mechanical properties, ensures the structural integrity of the battery pole plate after cyclic charging and discharging, improves the energy density of the battery, extends the battery life and improves the safety of use.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003614476430000271
    Figure BDA0003614476430000271
  • Figure BDA0003614476430000281
    Figure BDA0003614476430000281
Patent Text Reader

Abstract

The present invention provides a battery binder and a preparation method and application thereof. The battery binder comprises a block copolymer composed of a block A and a block B. The raw materials for preparing the block A comprise aromatic diisocyanate and aromatic diamine, and the raw materials for preparing the block B comprise aliphatic diisocyanate and aliphatic diamine. The battery binder has both excellent bonding performance and flexibility, and can ensure that the prepared battery pole piece has excellent mechanical properties, thereby enabling the further prepared battery to have excellent electrical properties. The preparation method of the battery binder is simple, the preparation conditions are mild, and the battery is suitable for large-scale industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of adhesives, and in particular relates to an adhesive for batteries and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery binders are inactive components in batteries. They account for a relatively small proportion in lithium-ion batteries, but they connect active materials, conductive agents, current collectors and other materials into a whole. They play a vital role in ensuring that the electrode has good mechanical properties and processing performance and maintaining the integrity of the conductive network of the battery during the charging and discharging process.

[0003] At present, the most widely used oil-soluble binder in lithium-ion batteries is polyvinylidene fluoride (PVDF). However, PVDF has a series of problems that are difficult to solve. For example, the monomers used to synthesize PVDF belong to fluorine-containing hydrocarbon compounds, so they will damage the earth's ozone layer. Therefore, its production is strictly controlled. In addition, the modulus of PVDF is large, which will cause the pole piece to be brittle. When it is used in large curvature bending applications, the active material is prone to falling off or powdering. The bonding force of PVDF mainly comes from the interfacial effect of weak van der Waals forces, which makes it difficult to effectively maintain the integrity of the electrode structure. It will cause the pole piece to easily degrade or have other side reactions during the charge and discharge cycle and high-temperature operation, causing electrode collapse. Therefore, PVDF has been unable to adapt to the demand for binders in today's rapidly developing new energy technologies.

[0004] CN105514488A discloses a lithium-ion battery binder and a lithium-ion battery containing the binder, the number average molecular weight of which is 500,000 to 1.2 million; the binder can greatly improve the flexibility of the positive electrode plate, avoid processing and battery performance problems caused by the brittleness of the plate, and is conducive to improving the compaction density and the energy density of the battery. Acrylate and acrylic acid structures are introduced into the chain structure of PVDF by copolymerization modification, thereby improving the flexibility of the plate. However, the main structural unit of the binder is still polyvinylidene fluoride, which still cannot fundamentally solve the defects of PVDF itself.

[0005] CN112186189A discloses a binder for a high-nickel ternary material positive electrode sheet, wherein the binder is a polyurethane fiber, which is a multi-block copolymer composed of alternating soft segments and hard segments. Compared with traditional PVDF, the binder provided by the invention can be thinly and evenly coated on the surface of the high-nickel ternary material, which effectively avoids the side reaction between the high-nickel material and the electrolyte during the charge and discharge process, while improving the stability of the positive electrode-electrolyte interface (CEI), and ensuring the cycle performance and safety performance of the high-nickel ternary system; on the other hand, the binder also helps the conductive agent to be more evenly distributed in the electrode, and to improve the overall conductivity of the battery to a greater extent, so as to improve the cycle performance of the battery, and solve the cycle performance and safety performance problems of the high-nickel ternary material battery due to the increase in nickel content. However, the binder provided by the invention has a strong water absorption, and thus has high processing requirements for the positive electrode slurry, a complex preparation method and harsh conditions, and there are also problems of high raw materials and production costs.

[0006] CN113773419A discloses a mussel biomimetic polymer and its preparation method, positive electrode binder, and secondary battery. The mussel biomimetic polymer provided by the invention has a dopamine structure and a carboxyl group, so it has a strong adhesion to the metal current collector and the positive electrode active material. When used as a positive electrode binder, it can improve the cycle performance, rate performance, and conductivity of the obtained positive electrode material, positive electrode, and secondary battery. However, the electrochemical stability of the hydroxyl group in the dopamine structure is poor, and it is easy to produce gas by electrochemical reaction, which is difficult to adapt to the high-voltage battery system, and dopamine is expensive and difficult to industrialize.

[0007] Therefore, developing a battery adhesive with both excellent bonding performance and flexibility is a technical problem that urgently needs to be solved in this field. Summary of the invention

[0008] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a battery binder and a preparation method and application thereof; the battery binder includes a block copolymer composed of a block A and a block B; the raw materials for preparing the block A include aromatic diisocyanate and aromatic diamine; the raw materials for preparing the block B include aliphatic diisocyanate and aliphatic diamine. The battery binder containing the block copolymer has both strong bonding strength and flexibility, so that the battery pole piece prepared by using the binder has excellent mechanical properties, thereby ensuring that the battery pole piece still has integrity after cyclic charge and discharge, improving the energy density of the battery pole piece, and thus improving the life and safety of the battery.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a battery binder, the battery binder comprising a block copolymer consisting of a block A and a block B;

[0011] The raw materials for preparing the block A include aromatic diisocyanate and aromatic diamine;

[0012] The raw materials for preparing the block B include aliphatic diisocyanate and aliphatic diamine.

[0013] The battery binder provided by the present invention includes a block copolymer composed of a block A and a block B; wherein the block A is a rigid block, and the raw materials for preparation include aromatic diisocyanate and aromatic diamine, and the block A can provide the toughness required by the binder, maintain the mechanical strength required by the binder, and also help to improve the tolerance of the binder to the electrolyte, and ensure the integrity of the binder; the block B is a flexible block, and the raw materials for preparation include aliphatic diisocyanate and aliphatic diamine, and the block B can provide the flexibility required by the binder, improve the wetting ability of the binder to the substrate, thereby improving the bonding force between the binder and the substrate, and can also give the binder a certain electrolyte swelling property, improve the rate of lithium ion transmission, and thus help to reduce the impedance of the pole piece. Therefore, the battery binder provided by the present invention, which includes block A and block B, has both strong bonding strength and flexibility, and while ensuring that the prepared battery pole piece has high mechanical properties, it can also maintain the structural integrity of the battery pole piece after cyclic charge and discharge, thereby greatly improving the energy density of the battery, and improving the battery life and safety of use.

[0014] Preferably, the molar ratio of block A to block B is 1:(0.4-4), for example, 1:0.8, 1:1.2, 1:1.6, 1:2, 1:2.4, 1:2.8, 1:3.2 or 1:3.6, and more preferably 1:(1-2.5).

[0015] As a preferred technical solution of the present invention, when the molar ratio of block A to block B is 1:(0.4-4), especially when the molar ratio is 1:(1-2.5), the flexibility of the obtained battery binder and its bonding ability to the substrate can be further improved, thereby further improving the electrical performance of the battery prepared by the battery binder.

[0016] Preferably, the molar percentage of aromatic diisocyanate in the raw material for preparing the block A is 30-49 mol%, for example, 32 mol%, 34 mol%, 36 mol%, 38 mol%, 40 mol%, 42 mol%, 44 mol%, 46 mol% or 48 mol%.

[0017] Preferably, the aromatic diisocyanate includes any one or a combination of at least two of 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, xylylene diisocyanate, dimethylbiphenyl diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate or 3,3-dichlorobiphenyl-4,4-diisocyanate.

[0018] Preferably, the molar percentage of the aromatic diamine in the raw material for preparing the block A is 51-70 mol%, for example, 52 mol%, 54 mol%, 56 mol%, 58 mol%, 60 mol%, 62 mol%, 64 mol%, 66 mol% or 68 mol%.

[0019] Preferably, the aromatic diamine includes any one of p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl or 5-amino-2-(4-aminophenyl)benzimidazole, or a combination of at least two thereof.

[0020] Preferably, the block A is prepared by the following method, which comprises: reacting an aromatic diisocyanate and an aromatic diamine in a solvent to obtain the block A.

[0021] Preferably, the solvent comprises N-methylpyrrolidone.

[0022] Preferably, the reaction time is 60 to 360 min, for example, 80 min, 120 min, 160 min, 200 min, 240 min, 280 min, 320 min or 340 min.

[0023] Preferably, the reaction temperature is 50-70°C, for example, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C or 68°C.

[0024] Preferably, the method specifically comprises the following steps:

[0025] (A1) dissolving an aromatic diisocyanate in a solvent to obtain an aromatic diisocyanate solution; dissolving an aromatic diamine in a solvent to obtain an aromatic diamine solution;

[0026] (A2) adding the aromatic diisocyanate solution in step (A1) to the aromatic diamine solution in step (A1) to react to obtain the block A.

[0027] Preferably, the mass percentage of the aromatic diisocyanate in the aromatic diisocyanate solution in step (A1) is 10-40%, for example, 13%, 16%, 19%, 22%, 25%, 28%, 31%, 34% or 37%, etc.

[0028] Preferably, the mass percentage of the aromatic diamine in the aromatic diamine solution in step (A1) is 10-40%, for example, 13%, 16%, 19%, 22%, 25%, 28%, 31%, 34% or 37%, etc.

[0029] Preferably, the adding time in step (A2) is 30 to 120 min, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min or 110 min, etc.

[0030] Preferably, the molar percentage of aliphatic diisocyanate in the raw materials for preparing block B is 51-70 mol%, for example, 52 mol%, 54 mol%, 56 mol%, 58 mol%, 60 mol%, 62 mol%, 64 mol%, 66 mol% or 68 mol%.

[0031] Preferably, the aliphatic diisocyanate includes any one of hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate or lysine diisocyanate, or a combination of at least two thereof.

[0032] Preferably, the molar percentage of the aliphatic diamine in the raw material for preparing the block B is 30-49 mol%, for example, 32 mol%, 34 mol%, 36 mol%, 38 mol%, 40 mol%, 42 mol%, 44 mol%, 46 mol% or 48 mol%.

[0033] Preferably, the aliphatic diamine includes any one of aliphatic carbon chain diamine, ether diamine, double amino-terminated polyamide or double amino-terminated polybutadiene-acrylonitrile copolymer, or a combination of at least two thereof.

[0034] Preferably, the aliphatic carbon chain diamine includes 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,36-triacontanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl-1,6-hexanediamine, 2,2-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-diethyl-1,6-hexanediamine, 2,2-dimethyl-1 ,7-heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine or 5-methyl-1,9-nonanediamine, or a combination of at least two thereof.

[0035] Preferably, the ether-based diamine includes any one of bis(2-aminoethyl) ether, 3,6-dioxa-1,8-octanediamine, 4,7-dioxa-1,10-decanediamine, 4,7-dioxa-2,9-decanediamine, 4,9-dioxa-1,12-dodecanediamine, 5,8-dioxa-3,10-dodecanediamine, 4,7,10-trioxa-1,13-tridecanediamine, bis(3-aminopropyl)polytetrahydrofuran or polyoxyalkylene diamine, or a combination of at least two thereof.

[0036] In the present invention, there is no particular limitation on the specific type of the polyoxyalkylene diamine, and commercially available products from Huntsman Company can generally be selected. D230, D400, D2000, D4000, XTJ511, XTJ523, XTJ536, XTJ542, XTJ559, XTJ568, XTJ569, ED600, ED900, ED2003, Polyetheramine D230, Polyetheramine D400, Polyetheramine D2000 from BASF, PC from Nitroil DA250, PC DA400, PC DA650 or PC Any one or a combination of at least two of DA2000.

[0037] Preferably, the double amino-terminated polyamide includes any one of double amino-terminated polyamide 6, double amino-terminated polyamide 11, double amino-terminated polyamide 12, double amino-terminated polyamide 66, double amino-terminated polyamide 610, double amino-terminated polyamide 612, double amino-terminated polyamide 1010, double amino-terminated polyamide 1011, double amino-terminated polyamide 1012, double amino-terminated polyamide 1013, double amino-terminated polyamide 1111, double amino-terminated polyamide 1112, double amino-terminated polyamide 1113, double amino-terminated polyamide 1212, double amino-terminated polyamide 1213, double amino-terminated polyamide 1313 or double amino-terminated polyamide 1414, or a combination of at least two of them.

[0038] Preferably, the number of carbon atoms on the main chain of the aliphatic diamine is greater than 10, for example, 11, 12, 13, 14, 15, 16, 17, 18, 19 or 20.

[0039] As a preferred technical solution of the present invention, in the present invention, the aliphatic diamine is preferably an aliphatic diamine having more than 10 carbon atoms in the main chain, so that the block B can have better flexibility.

[0040] Preferably, the block B is prepared by the following method, which comprises: reacting an aliphatic diisocyanate and an aliphatic diamine in a solvent to obtain the block B.

[0041] Preferably, the solvent comprises N-methylpyrrolidone.

[0042] Preferably, the reaction time is 60 to 360 min, for example, 80 min, 120 min, 160 min, 200 min, 240 min, 280 min, 320 min or 340 min.

[0043] Preferably, the reaction temperature is 50-70°C, for example, 52°C, 54°C, 56°C, 58°C, 60°C, 62°C, 64°C, 66°C or 68°C.

[0044] Preferably, the method specifically comprises the following steps:

[0045] (B1) dissolving an aliphatic diisocyanate in a solvent to obtain an aliphatic diisocyanate solution; dissolving an aliphatic diamine in a solvent to obtain an aliphatic diamine solution;

[0046] (B2) adding the aliphatic diisocyanate solution in step (B1) to the aliphatic diamine solution in step (B1) to react and obtain the block B.

[0047] Preferably, the mass percentage of the aliphatic diisocyanate in the aliphatic diisocyanate solution in step (B1) is 10-40%, for example, 13%, 16%, 19%, 22%, 25%, 28%, 31%, 34% or 37%, etc.

[0048] Preferably, the mass percentage of the aliphatic diamine in the aliphatic diamine solution in step (B1) is 10-40%, for example, 13%, 16%, 19%, 22%, 25%, 28%, 31%, 34% or 37%, etc.

[0049] Preferably, the adding time in step (B2) is 30 to 60 min, for example, 33 min, 36 min, 39 min, 42 min, 45 min, 48 min, 51 min, 54 min, 57 min or 60 min, etc.

[0050] Preferably, the viscosity of the block copolymer is 100 to 100,000 mPa·s, for example, 500 mPa·s, 1,000 mPa·s, 3,000 mPa·s, 6,000 mPa·s, 9,000 mPa·s, 10,000 mPa·s, 30,000 mPa·s, 60,000 mPa·s or 90,000 mPa·s, and more preferably 1,000 to 10,000 mPa·s.

[0051] As a preferred technical solution of the present invention, a battery binder containing a block copolymer with a viscosity of 1000 to 100000 mPa·s can effectively improve the processing performance and coating appearance of the slurry. On the one hand, if the viscosity of the block copolymer is low, it will lead to insufficient self-suspension performance, which will lead to sedimentation of the slurry, reduce the peeling strength of the pole piece, and cause the active material layer in the pole piece to fall due to insufficient cohesion; on the other hand, if the viscosity of the block copolymer is high, it will lead to difficulties in slurry processing and coating, and slurry dispersion, resulting in pitting, scratches or particles on the surface of the active material layer of the pole piece.

[0052] It should be noted that the "viscosity" of the block copolymer refers to the viscosity of the block copolymer measured in N-methylpyrrolidone at a mass concentration of 10% at 25±0.01°C.

[0053] Preferably, the glass transition temperature of the block copolymer is -20 to 160°C, such as 0°C, 20°C, 40°C, 60°C, 80°C, 100°C, 120°C or 140°C, and more preferably 40 to 120°C.

[0054] As a preferred technical solution of the present invention, selecting a block copolymer with a glass transition temperature of -20 to 160°C is beneficial to making the battery adhesive have better bonding performance and better electrolyte resistance; on the one hand, if the glass transition temperature of the block copolymer is too low, it will lead to insufficient mechanical properties of the battery adhesive, making it difficult to maintain the integrity of the overall structure of the electrode, and will also cause the electrode's electrolyte resistance to decline, which is not conducive to the long cycle performance of the battery; on the other hand, if the glass transition temperature of the block copolymer is too high, it will cause the battery adhesive to be too hard and brittle, further causing the electrode to easily break and fail during processing, and will also cause the peel strength of the electrode to drop significantly, thereby causing the electrode active material layer to lose powder due to insufficient cohesion.

[0055] Preferably, the elastic modulus of the block copolymer is 500-4000 MPa, such as 1000 MPa, 1500 MPa, 2000 MPa, 2500 MPa, 3000 MPa or 3500 MPa, more preferably 800-3000 MPa, and even more preferably 1200-2500 MPa.

[0056] As a preferred technical solution of the present invention, the selection of a block copolymer with an elastic modulus of 500 to 4000 MPa is conducive to obtaining a battery binder with better flexibility. On the one hand, if the elastic modulus of the block copolymer is too low, the mechanical properties of the battery binder will be insufficient, making it difficult to maintain the integrity of the overall structure of the pole piece; on the other hand, if the elastic modulus of the block copolymer is too high, the battery binder will be too hard and brittle, and the pole piece will easily break and fail during the processing of the pole piece.

[0057] Preferably, the battery binder further includes a binder material and / or a conductive material.

[0058] Preferably, based on 100 parts by total weight of the battery binder, the content of the adhesive material is 1 to 49 parts by weight, for example, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight or 45 parts by weight.

[0059] Preferably, the bonding material includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride copolymer, polytetrafluoroethylene copolymer, polyimide, polyetherimide, polyamideimide, polyesterimide, polycarbonateimide, polyureaimide, styrene-butadiene rubber, polyacrylonitrile, polyacrylic acid, polyacrylate, polyacrylic acid-polyacrylonitrile copolymer or polyacrylate-polyacrylonitrile copolymer, or a combination of at least two thereof.

[0060] Preferably, the bonding material includes any one of polyvinylidene fluoride, polyimide, polyamide-imide, polyacrylic acid or styrene-butadiene rubber, or a combination of at least two thereof.

[0061] Preferably, based on 100 parts by total weight of the battery binder, the content of the conductive material is 1 to 49 parts by weight, for example, 5 parts by weight, 10 parts by weight, 15 parts by weight, 20 parts by weight, 25 parts by weight, 30 parts by weight, 35 parts by weight, 40 parts by weight or 45 parts by weight.

[0062] Preferably, the conductive material includes any one of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, carbon nanotubes, carbon fibers, graphene or conductive polymers, or a combination of at least two thereof.

[0063] In a second aspect, the present invention provides a method for preparing the battery binder as described in the first aspect, the preparation method comprising the following steps:

[0064] (1) mixing block A and block B, reacting to obtain an intermediate product;

[0065] (2) Adding a chain extender to the intermediate product obtained in step (1) to carry out a reaction, and then adding a capping agent to carry out a reaction to obtain the battery binder.

[0066] The preparation method of the battery binder provided by the present invention is obtained through step-by-step polymerization reaction, the overall preparation method is simple, the conditions are mild, and it is suitable for large-scale industrial production.

[0067] Preferably, the mixing in step (1) is performed by adding block A to block B.

[0068] Preferably, the adding time is 60 to 360 min, for example, 100 min, 140 min, 180 min, 220 min, 260 min, 300 min or 340 min.

[0069] Specifically, in step (1) of the preparation method provided by the present invention, a solution containing block A (N-methylpyrrolidone solution of block A) can be added to a solution containing block B (N-methylpyrrolidone solution of block B) within 60 to 360 minutes for mixing to obtain a mixed solution; controlling the addition time within 60 to 360 minutes will make the final battery binder have the best comprehensive performance; on the one hand, if the addition time is too short, it is easy to cause the reaction to be too violent and the final binder to deteriorate; on the other hand, if the addition time is too long, it will lead to a slow reaction process and a decrease in production efficiency.

[0070] Preferably, the reaction time of step (1) is 60 to 360 min, for example, 100 min, 140 min, 180 min, 220 min, 260 min, 300 min or 340 min.

[0071] As a preferred technical solution of the present invention, the reaction time of step (1) is 60 to 360 minutes. If the reaction time is too short, it is easy to cause insufficient conversion rate of the reaction unit, resulting in reduced performance of the final battery binder.

[0072] Preferably, the reaction temperature in step (1) is 60-90°C, for example, 63°C, 66°C, 69°C, 72°C, 75°C, 78°C, 81°C, 84°C or 87°C.

[0073] As a preferred technical solution of the present invention, the reaction temperature of step (1) is 60-90°C, which makes the final battery binder have the best comprehensive performance. On the one hand, when the reaction temperature is lower than 60°C, the reaction process will be slow and the production efficiency will be reduced; on the other hand, when the reaction temperature is higher than 90°C, it is easy to cause the reaction to be too intense and the battery binder to deteriorate; when the reaction time of the stage is shorter than the range of the present invention, it is easy to cause insufficient reaction unit conversion rate and reduced binder performance.

[0074] Preferably, the amount of the chain extender added in step (2) is 0.2-2% of the total mass of block A and block B, for example 0.4%, 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6% or 1.8%, etc.

[0075] Preferably, the chain extender in step (2) is an aliphatic diamine.

[0076] Preferably, the temperature for reacting by adding the chain extender in step (2) is 60-90°C, for example, 63°C, 66°C, 69°C, 72°C, 75°C, 78°C, 81°C, 84°C or 87°C.

[0077] Preferably, the reaction time of adding the chain extender in step (2) is 30 to 120 min, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min or 120 min.

[0078] Preferably, the amount of the end-capping agent added in step (2) is 0.1-1% of the total mass of block A and block B, such as 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8% or 0.9%.

[0079] Preferably, the end-capping agent in step (2) comprises any one of methylamine, ethylamine, propylamine, dimethylamine, diethylamine, aniline, diphenylamine or p-aminobenzoic acid, or a combination of at least two thereof.

[0080] Preferably, the reaction time of adding the end-capping agent in step (2) is 30 to 120 min, for example, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min or 110 min.

[0081] Preferably, the temperature for reacting by adding the end-capping agent in step (2) is 20-40°C, for example, 22°C, 24°C, 26°C, 28°C, 30°C, 32°C, 34°C, 36°C or 38°C.

[0082] Preferably, before adding the end-capping agent in step (2), the step of adding N-methylpyrrolidone for dilution is also included.

[0083] As a preferred technical solution, the preparation method comprises the following steps:

[0084] (1) adding a solution containing block A to a solution containing block B within 60 to 360 minutes, reacting at 60 to 90° C. for 60 to 360 minutes to obtain an intermediate product;

[0085] (2) adding a chain extender to the intermediate product obtained in step (1) and reacting at 60 to 90° C. for 30 to 120 min, adding N-methylpyrrolidone to dilute, cooling to 25 to 35° C., and then adding a capping agent to react for 30 to 120 min to obtain the battery binder;

[0086] In a third aspect, the present invention provides a battery pole piece, wherein the battery pole piece includes the battery binder as described in the first aspect.

[0087] Preferably, the battery electrode is a positive electrode or a negative electrode.

[0088] It should be noted that in actual application, the battery binder provided by the present invention can also be applied to the positive electrode material of the battery, the edge of the positive electrode, the bottom of the positive electrode, the negative electrode material, the edge of the negative electrode, the bottom of the negative electrode and the separator.

[0089] When the battery binder provided by the present invention is applied to the positive electrode sheet and the negative electrode sheet of the battery, there is no particular limitation on the type of active material selected in the positive electrode sheet or the negative electrode sheet, and there is no particular limitation on the particle size of the active material. Regarding the positive electrode active material used, it may include but is not limited to any one or more combinations of lithium iron phosphorus oxide, lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium iron oxide, lithium nickel manganese oxide, lithium cobalt nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and their composites; regarding the negative electrode active material used, it may include but is not limited to one or more of carbon / silicon materials, metals and metal oxides; the carbon / silicon material, for example, may use any one or more combinations of natural graphite, artificial graphite, amorphous carbon, diamond-like carbon, carbon nanotubes, carbon / silicon hybrid materials, silicon oxide, silicon; the metal may include but is not limited to one of lithium, aluminum, tin, silver, zinc, calcium, barium, mercury, platinum, technetium, bismuth, indium or a metal alloy containing two or more of them; the metal oxide may include but is not limited to one or more of aluminum oxide, tin oxide, indium oxide, zinc oxide and lithium oxide.

[0090] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the battery electrode sheet as described in the third aspect.

[0091] Compared with the prior art, the present invention has the following beneficial effects:

[0092] (1) The battery binder provided by the present invention comprises a block copolymer composed of block A and block B, wherein the raw materials for preparing the block A include aromatic diisocyanate and aromatic diamine, and the raw materials for preparing the block B include aliphatic diisocyanate and aliphatic diamine. The block A is a rigid block containing a strong polar group, and the block B is a flexible block B. The battery binder provided by the present invention comprises a block copolymer composed of block A and block B. Therefore, it combines the advantages of the above-mentioned block A and block B, and has excellent flexibility and bonding properties. When applied to battery pole pieces, the battery pole pieces can have excellent mechanical properties, and thus the battery containing the battery pole pieces has excellent electrical properties. Specifically, the peel strength of the positive electrode sheet obtained by using the battery binder provided by the present invention is 9 to 36 N / m, and the internal resistance of the soft-pack battery further prepared is 294 to 870 mΩ, and the capacity retention rate after 100 cycles is 94.8 to 99.4%.

[0093] (2) The block copolymer contained in the battery binder provided by the present invention can be obtained by a step-by-step polymerization reaction. The overall preparation method is simple, the conditions are mild, and it is suitable for large-scale industrialization. The prepared binder can also improve the dispersibility of the electrode slurry, improve the processing problems that are prone to occur during the coating process when using small-particle materials, and at the same time improve the adhesion between the binder and the polymer, between the polymer and the active material, between the polymer and the conductive agent, and between the polymer and the current collector, which has important research value. DETAILED DESCRIPTION

[0094] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0095] Example 1

[0096] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 5:5;

[0097] The preparation method of the block copolymer comprises the following steps:

[0098] (1) Synthesis of block A: 105 g (42 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 245 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 62.7 g (58 mol%) of m-phenylenediamine was dissolved in 146 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0099] (2) Synthesis of block B: 97.6 g (58 mol%) of hexamethylene diisocyanate was dissolved in 228 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 72.4 g (42 mol%) of 1,10-decanediamine was dissolved in 169 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%; then the B1 solution was uniformly added to the B2 solution over 40 minutes, and the mixture was stirred and reacted, and the temperature of the mixed reaction solution was maintained at 60° C. and the reaction was continued for 180 minutes to form a block B solution;

[0100] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes, and the mixture was stirred and mixed. The temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 5:5. Then, 3.38 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to the intermediate to carry out a chain extension reaction for 60 minutes, and then 2291 g of N-methylpyrrolidone was added for dilution. After the temperature of the mixed reaction liquid was reduced to 30° C., 1.02 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was carried out for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0101] Example 2

[0102] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 5:5;

[0103] The preparation method of the block copolymer comprises the following steps:

[0104] (1) Synthesis of block A: 105 g (42 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 245 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 115 g (58 mol%) of 4,4'-diaminodiphenylmethane was dissolved in 268 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0105] (2) Synthesis of Block B: 97.6 g (58 mol%) of hexamethylene diisocyanate was dissolved in 228 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 168 g (42 mol%) of ether diamine D400 was dissolved in 392g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%; then the B1 solution was uniformly added to the B2 solution for stirring and mixing within 60min, and the temperature of the mixed reaction solution was maintained at 50°C and the reaction was continued for 270min to form a block B solution;

[0106] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes, and the mixture was stirred and mixed. The temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 5:5. Then, 9.71 g (accounting for 2% of the total mass of block A and block B) of 1,12-dodecanediamine was added to the intermediate to carry out chain extension reaction for 60 minutes, and 3352 g of N-methylpyrrolidone was added for dilution. After the temperature of the mixed reaction liquid was reduced to 30° C., 2.97 g (mass content of 0.6%) of aniline end-capping agent was added and the mixture was reacted for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0107] Example 3

[0108] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 5:5;

[0109] The preparation method of the block copolymer comprises the following steps:

[0110] (1) Synthesis of block A: 85.3 g (49 mol%) of toluene diisocyanate was dissolved in 128 g of N-methylpyrrolidone to form an A1 solution with a mass content of 40%; 126.6 g (51 mol%) of 4,4'-diaminodiphenyl sulfone was dissolved in 1139.7 g of N-methylpyrrolidone to form an A2 solution with a mass content of 10%; then the A1 solution was uniformly added to the A2 solution over 60 min, and the mixed reaction solution was maintained at 50° C. under stirring and reacted for 360 min to form a block A solution;

[0111] (2) Synthesis of block B: 117.8 g (53 mol%) of isophorone diisocyanate was dissolved in 176.7 g of N-methylpyrrolidone to form a B1 solution with a mass content of 40%; 752 g (47 mol%) of double-terminated amino polybutadiene-acrylonitrile copolymer (from Noveon, USA, model 1300×16) was dissolved in 1128 g of N-methylpyrrolidone to form a B2 solution with a mass content of 40%. Then, the B1 solution was uniformly added to the B2 solution over 60 minutes, stirred and mixed, and the temperature of the mixed reaction liquid was maintained at 70°C and the reaction was continued for 60 minutes to form a block B solution;

[0112] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 270 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 80° C. and the reaction was continued for 360 minutes to form an intermediate with a molar ratio of block A to block B of 5:5, and then 2.16 g (accounting for 0.2% of the total mass of block A and block B) of bis(2-aminoethyl) ether was added to the intermediate to carry out chain extension reaction for 30 minutes, and 7293 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 10.8 g (mass content of 1%) of p-aminobenzoic acid end-capping agent was added and the reaction was carried out for 120 minutes to obtain a block copolymer with a solid content of 10%.

[0113] Example 4

[0114] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 5:5;

[0115] The preparation method of the block copolymer comprises the following steps:

[0116] (1) Synthesis of block A: 56.5 g (30 mol%) of xylene diisocyanate was dissolved in 508.1 g of N-methylpyrrolidone to form an A1 solution with a mass content of 10%; 140.2 g (70 mol%) of 4,4'-diaminodiphenyl ether was dissolved in 210.3 g of N-methylpyrrolidone to form an A2 solution with a mass content of 40%; then the A1 solution was uniformly added to the A2 solution over 30 minutes, and the mixed reaction solution was maintained at 70° C. under stirring and reacted for 60 minutes to form a block A solution;

[0117] (2) Synthesis of block B: 183.6 g (70 mol%) of dicyclohexylmethane diisocyanate was dissolved in 734.6 g of N-methylpyrrolidone to form a B1 solution with a mass content of 20%; 480 g (30 mol%) of double-terminated amino polybutadiene-acrylonitrile copolymer (Noveon, USA, model 1300×16) was dissolved in 720 g of N-methylpyrrolidone to form a B2 solution with a mass content of 40%. Then, the B1 solution was uniformly added to the B2 solution over 60 minutes, stirred and mixed, and the temperature of the mixed reaction liquid was maintained at 60°C and the reaction was continued for 240 minutes to form a block B solution;

[0118] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 120 minutes, and the mixture was stirred and reacted; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 300 minutes to form an intermediate with a molar ratio of block A to block B of 5:5, and then 1.72 g (accounting for 0.2% of the total mass of block A and block B) of bis(2-aminoethyl) ether was added to carry out chain extension reaction for 120 minutes, and 5593 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 0.86 g (mass content of 0.1%) of diethylamine end-capping agent was added and the reaction was carried out for 120 minutes to obtain a block copolymer with a solid content of 10%.

[0119] Example 5

[0120] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 2:8;

[0121] The preparation method of the block copolymer comprises the following steps:

[0122] (1) Synthesis of block A: 49 g (49 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 114 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 22.1 g (51 mol%) of m-phenylenediamine was dissolved in 51.5 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0123] (2) Synthesis of block B: 137.2 g (51 mol%) of hexamethylene diisocyanate was dissolved in 320.2 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 135.1 g (49 mol%) of 1,10-decanediamine was dissolved in 315.2 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution over 40 minutes, and the mixture was stirred and reacted. The temperature of the mixed reaction solution was maintained at 60°C and the reaction was continued for 180 minutes to form a block B solution;

[0124] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 2:8, and then 3.43 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to carry out chain extension reaction for 60 minutes, and 2330 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 1.04 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was continued for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0125] Example 6

[0126] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 7:3;

[0127] The preparation method of the block copolymer comprises the following steps:

[0128] (1) Synthesis of block A: 171.7 g (49 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 401 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 77.2 g (51 mol%) of m-phenylenediamine was dissolved in 180 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0129] (2) Synthesis of block B: 51.5 g (51 mol%) of hexamethylene diisocyanate was dissolved in 120 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 50.7 g (49 mol%) of 1,10-decanediamine was dissolved in 118.2 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution over 40 minutes, and the mixture was stirred and reacted. The temperature of the mixed reaction solution was maintained at 60°C and the reaction was continued for 180 minutes to form a block B solution;

[0130] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 7:3, and then 3.51 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to carry out chain extension reaction for 60 minutes, and 2381 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 1.06 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was carried out for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0131] Example 7

[0132] A battery binder, comprising 90 parts by weight of a block copolymer and 10 parts by weight of a polyamide-imide;

[0133] Wherein, the block copolymer is the block copolymer obtained in Example 1;

[0134] The preparation method of polyamide-imide is prepared by referring to patent CN113571704A.

[0135] Example 8

[0136] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 9:1;

[0137] The preparation method of the block copolymer comprises the following steps:

[0138] (1) Synthesis of block A: 189 g (42 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 441 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 113 g (58 mol%) of m-phenylenediamine was dissolved in 263 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0139] (2) Synthesis of block B: 19.5 g (58 mol%) of hexamethylene diisocyanate was dissolved in 45.5 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 14.5 g (42 mol%) of 1,10-decanediamine was dissolved in 33.8 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution over 40 minutes, and the mixture was stirred and reacted. The temperature of the mixed reaction liquid was maintained at 60°C and the reaction was continued for 180 minutes to form a block B solution;

[0140] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 9:1, and then 3.36 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to carry out chain extension reaction for 60 minutes, and 2280 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 1.02 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was carried out for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0141] Example 9

[0142] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 1:5;

[0143] The preparation method of the block copolymer comprises the following steps:

[0144] (1) Synthesis of block A: 24.5 g (49 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 57.2 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 11.0 g (51 mol%) of m-phenylenediamine was dissolved in 25.7 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0145] (2) Synthesis of block B: 85.8 g (51 mol%) of hexamethylene diisocyanate was dissolved in 200 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 84.4 g (49 mol%) of 1,10-decanediamine was dissolved in 197 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution over 40 minutes, stirred and mixed, and the temperature of the mixed reaction liquid was maintained at 60°C and the reaction was continued for 180 minutes to form a block B solution;

[0146] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 1:5, and then 2.06 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to carry out chain extension reaction for 60 minutes, and 1396 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 0.62 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was carried out for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0147] Example 10

[0148] A battery binder, wherein the battery binder is a block copolymer formed by a block A and a block B in a molar ratio of 2:8;

[0149] The preparation method of the block copolymer comprises the following steps:

[0150] (1) Synthesis of block A: 49.0 g (49 mol%) of 4,4'-diphenylmethane diisocyanate was dissolved in 114 g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; 83.7 g (51 mol%) of 2,2-bis[4-(4-aminophenoxy)phenyl]propane was dissolved in 195 g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; then the A1 solution was uniformly added to the A2 solution within 60 min, and the mixed reaction solution was maintained at 60° C. under stirring and reacted for 300 min to form a block A solution;

[0151] (2) Synthesis of block B: 137 g (51 mol%) of hexamethylene diisocyanate was dissolved in 320 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; 1254 g (49 mol%) of double-terminated amino polybutadiene-acrylonitrile copolymer (Noveon, USA, model 1300×16) was dissolved in 2927 g of N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution over 40 minutes, stirred and mixed, and the temperature of the mixed reaction liquid was maintained at 60°C and the reaction was continued for 180 minutes to form a block B solution;

[0152] (3) Synthesis of block copolymer: The block A solution obtained in step (1) was uniformly added to the block B solution obtained in step (2) over 180 minutes to stir and react; the temperature of the mixed reaction liquid was maintained at 70° C. and the reaction was continued for 240 minutes to form an intermediate with a molar ratio of block A to block B of 2:8, and then 15.2 g (1% of the total mass of block A and block B) of 1,6-hexanediamine was added to carry out chain extension reaction for 60 minutes, and 10342 g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30° C., 4.62 g (mass content of 0.3%) of propylamine end-capping agent was added and the reaction was carried out for 60 minutes to obtain a block copolymer with a solid content of 10%.

[0153] Comparative Example 1

[0154] A battery binder, wherein the battery binder is a random copolymer;

[0155] The preparation method of the random copolymer comprises: dissolving 105g of 4,4'-diphenylmethane diisocyanate in 245g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%, dissolving 97.6g of hexamethylene diisocyanate in 228g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%, and then uniformly mixing the A1 solution and the B1 solution; dissolving 62.7g of m-phenylenediamine in 146g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%; dissolving 72.4g of 1,10-decanediamine in 169g of N-methylpyrrolidone was added to form a B2 solution with a mass content of 30%, and then the A2 solution and the B2 solution were mixed evenly, and then the mixed solution of the A1 solution and the B1 solution was uniformly added to the mixed solution of the A2 solution and the B2 solution within 180 minutes, and the mixed reaction liquid temperature was maintained at 70°C and continued to react for 240 minutes. Then 3.38g of 1,6-hexanediamine was added to carry out the chain extension reaction for 60 minutes, and 2291g of N-methylpyrrolidone was added for dilution. After the temperature of the mixed reaction liquid was reduced to 30°C, 1.02g of propylamine capping agent was added and reacted for 60 minutes to obtain a random copolymer solution with a solid content of 10%.

[0156] Comparative Example 2

[0157] A battery binder, wherein the battery binder is a polymer containing only block B;

[0158] The preparation method of the polymer containing only block B comprises: dissolving 85.8 g (51 mol%) of hexamethylene diisocyanate in 200 g of N-methylpyrrolidone to form a B1 solution with a mass content of 30%; D400 was dissolved in 457g N-methylpyrrolidone to form a B2 solution with a mass content of 30%. Then, the B1 solution was uniformly added to the B2 solution for stirring and mixing reaction within 40 minutes, and the temperature of the mixed reaction liquid was maintained at 60°C for 180 minutes. Then, 2.82g of 1,6-hexanediamine was added for chain extension reaction for 60 minutes, and 1912g of N-methylpyrrolidone was added for dilution; after the temperature of the mixed reaction liquid was reduced to 30°C, 0.85g of propylamine capping agent was added and reacted for 60 minutes to obtain a polymer containing only block B with a solid content of 10%.

[0159] Comparative Example 3

[0160] A battery binder, wherein the battery binder is a polymer containing only block A;

[0161] The preparation method of the polymer containing only block A includes: dissolving 128g (51mol%) of 4,4'-diphenylmethane diisocyanate in 298g of N-methylpyrrolidone to form an A1 solution with a mass content of 30%; dissolving 53g (49mol%) of m-phenylenediamine in 124g of N-methylpyrrolidone to form an A2 solution with a mass content of 30%. Then, the A1 solution is uniformly added to the A2 solution within 40min, stirred and mixed, and the temperature of the mixed reaction liquid is maintained at 60°C and the reaction is continued for 180min. Then, 1.81g of 1,6-hexanediamine is added to carry out a chain extension reaction for 60min, and 1225g of N-methylpyrrolidone is added for dilution; after the temperature of the mixed reaction liquid is reduced to 30°C, 0.55g of propylamine capping agent is added, and the reaction is carried out for 60min to obtain the battery binder.

[0162] Application Example 1

[0163] A soft pack battery, the preparation method of which comprises the following steps:

[0164] (1) Preparation of positive electrode sheet: Based on the solid weight, 95 parts of lithium iron phosphate (Bai Te Rui, P198-S13), 2.5 parts of Super P conductive carbon black, and 2.5 parts of battery binder (Example 1) were added with an appropriate amount of NMP at a ratio of 63% of the total solid content, mixed and stirred in a vacuum stirring tank, and dispersed evenly to prepare a battery slurry; the obtained battery slurry was filtered through a 100-mesh screen, and then the battery slurry was evenly coated on the front and back surfaces of the aluminum foil as the current collector using an extrusion coater, and the coated surface density was 350 g / m 2 , air drying is performed at 105°C to remove the solvent, and then rolling is performed at room temperature to form a positive electrode sheet;

[0165] (2) Preparation of negative electrode sheet: 96 parts of artificial graphite (B&T, S360), 1 part of carbon nanotubes (Cabot, GCNTs5), 1 part of CMC (Dow, CRT30000PA), and 2 parts of styrene-butadiene rubber latex (Japan JSR, TRD104A) were mixed and dispersed evenly with water as solvent to make negative electrode slurry, which was then coated on the front and back surfaces of copper foil and dried with air at 95°C to remove the solvent. Then, the negative electrode sheet was formed by rolling at room temperature;

[0166] (3) Welding conductive tabs on the obtained positive electrode sheet and negative electrode sheet, placing a polyethylene separator between the positive electrode sheet and the negative electrode sheet, winding it into a bare battery core and then wrapping it in an aluminum-plastic film, and injecting an electrolyte composed of EC:EMC:DEC volume ratio = 1:1:1 (containing 1.0M LiPF6), packaging and then forming the battery to obtain the soft-pack battery.

[0167] Application Examples 2 to 10

[0168] A soft-pack battery, which differs from Application Example 1 only in that the battery binder obtained in Examples 2 to 10 is used to replace the battery binder obtained in Example 1, and other substances, contents and preparation methods are the same as those in Application Example 1.

[0169] Comparative Application Examples 1 to 3

[0170] A soft-pack battery, which differs from Application Example 1 only in that the battery binder obtained in Comparative Examples 1 to 3 is used to replace the battery binder obtained in Example 1, and other substances, contents and preparation methods are the same as those in Application Example 1.

[0171] Performance Testing:

[0172] (1) Glass transition temperature: measured by differential scanning calorimetry (DSC) according to the test method provided in ASTM D3418; specifically, the sample was coated on a glass plate and dried in vacuum at 120°C to form a solid film. A NETZSCH DSC 204F1 Phoenix was used, with a test temperature range of -20 to 200°C and a heating rate of 10°C / min. The temperature was raised from -20°C to 200°C, and then the sample was cooled to -20°C at a rate of 10°C / min. A second heating process was performed 3 minutes later. The records of the second heating process were analyzed to obtain the glass transition temperature (Tg) of the sample;

[0173] (2) Elastic modulus: The prepared sample was coated on a glass plate, vacuum dried in a vacuum oven at 120°C, and then peeled off from the glass plate to obtain a polymer film of uniform thickness. The elastic modulus of the film was measured according to the test standard provided by ASTM D882; specifically, a universal electronic testing machine was used, the width of the film to be tested was 15 mm, the length was 200 mm, the tensile speed was 25 mm / min, and the average of the three test records was recorded as the final result.

[0174] The adhesives obtained in Examples 1 to 10 and Comparative Examples 1 to 3 were tested according to the above test methods (1) and (2). The test results are shown in Table 1:

[0175] Table 1

[0176] Glass transition temperature(℃) Elastic modulus (MPa) Example 1 115 2602 Example 2 95 2293 Example 3 25 1263 Example 4 40 1520 Example 5 55 1407 Example 6 160 3792 Example 7 110 2554 Example 8 >200 5028 Example 9 30 1291 Example 10 <-20 <200 Comparative Example 1 120 2686 Comparative Example 2 <-20 <200 Comparative Example 3 >200 5337

[0177] (3) Peel strength: The positive electrode sheet prepared in step (1) of the application example and the comparative application example was cut into 10×2 cm strips, fixed to a 1 mm thick steel plate with double-sided tape on the current collector side, and affixed with 3M tape on the coating layer side. A 180° pulling peeling test was performed at a peeling speed of 100 mm / min using a universal electronic testing machine at 25°C, and the average peeling stress was recorded.

[0178] (4) Internal resistance: The internal resistance of the soft-pack battery was tested using a Solartron electrochemical workstation;

[0179] (5) Cycling performance: The soft-pack battery prepared above was formed and divided into different capacities using a battery test cabinet; the formation step was to charge at a constant current of 0.05C for 2.0h, and then to charge at a constant current of 0.15C for 2.5h; the division step was to charge at a constant current of 0.33C to 4.2V, and then to charge at a constant voltage at 4.2V to a cut-off current of 0.02C, and to discharge at 0.33C to 2.5V; at 25°C, the divided battery was charged at a constant current of 0.33C to 4.2V, and then to a constant voltage to a cut-off current of 0.02C, left for 5min, and discharged at 0.33C. The battery was charged to 2.5 V and left for 5 min, and the discharge capacity after the first cycle was recorded; again, the battery was charged to 4.2 V at a constant current of 0.5 C, and then charged to a cut-off current of 0.02 C at a constant voltage, and left for 5 min, and then discharged to 2.5 V at 0.5 C and left for 5 min. After 100 cycles of charge / discharge, the discharge capacity after the 100th cycle was recorded. The capacity retention rate of the battery after 100 cycles was calculated using the following formula: Capacity retention rate after 100 cycles (%) = discharge capacity after the 100th cycle / discharge capacity after the first cycle.

[0180] The positive electrode sheets obtained from Examples 1 to 10 and Comparative Application Examples 1 to 3 were tested according to the above test method (3); the soft-pack batteries obtained from Examples 1 to 10 and Comparative Application Examples 1 to 3 were tested according to the above test methods (4) to (5). The test results are shown in Table 2:

[0181] Table 2

[0182]

[0183]

[0184] It can be seen from Table 1 and Table 2 that the peel strength of the positive electrode sheet obtained by using the binder provided by the present invention is 9-36 N / m (Application Examples 1-10), the internal resistance of the soft-pack battery prepared by using the above positive electrode sheet is 294-870 mΩ, and the capacity retention rate after 100 cycles is 94.8-99.4%.

[0185] By comparing Application Examples 1 to 10 and Comparative Application Example 1, it can be found that Comparative Application Example 1 uses the random polymer provided in Comparative Example 1 as a battery binder, while Application Examples 1 to 10 respectively use the block copolymers provided in Examples 1 to 10 as battery binders. In comparison, the pole pieces provided in Application Examples 1 to 10 have higher peel strength, so that the soft-pack batteries prepared therefrom have lower internal resistance and better cycle performance.

[0186] By comparing Application Examples 1 to 7 and Application Examples 2 to 3, it can be found that Application Example 2 uses the binder containing only block B provided in Example 2, so that although the bonding strength of the prepared electrode is relatively high, the internal resistance of the soft-pack battery prepared is increased and the cycle performance is reduced; Application Example 3 uses the binder containing only block A provided in Example 3, so the bonding strength of the prepared electrode is relatively low, and the internal resistance of the prepared soft-pack battery is relatively high, and the cycle performance is relatively poor.

[0187] Further comparison of Application Example 1 and Application Examples 8 to 9 shows that the battery binder provided in Example 8 used in Application Example 8 has a too high molar ratio of block A to block B in its block copolymer, which makes the glass transition temperature of the prepared binder too high and the modulus too large, which makes the peel strength of the electrode prepared by using it too low, and the internal resistance of the soft-pack battery further prepared is too high, and the cycle performance is poor; while the battery binder provided in Example 9 used in Application Example 9 has a too low molar ratio of block A to block B in its block copolymer, although the glass transition temperature and modulus of the prepared binder are within the obvious limit of this method, the internal resistance of the soft-pack battery further prepared is too high, and the cycle performance is poor.

[0188] Further comparison of Application Example 1 and Application Example 10 shows that although the molar ratio of block A to block B in the binder provided in Comparative Example 10 is within the preferred range described in the present invention, its glass transition temperature is too low and the modulus is too small. Therefore, the bonding strength of the prepared electrode is slightly reduced, the internal resistance of the prepared soft-pack battery is slightly increased, and the cycle performance is reduced.

[0189] In summary, the battery binder provided by the present invention contains a block copolymer consisting of block A and block B obtained by a step-by-step polymerization reaction, which can effectively improve the electrode peeling strength when using the block copolymer as a battery binder, reduce the internal resistance of the battery, and improve the battery cycle capacity retention rate.

[0190] The applicant declares that the present invention illustrates a battery binder and its preparation method and application through the above embodiments, but the present invention is not limited to the above embodiments, that is, it does not mean that the present invention must rely on the above embodiments to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A battery binder, characterized in that: The battery binder includes a block copolymer consisting of block A and block B; The raw materials for preparing the block A include aromatic diisocyanate and aromatic diamine; The raw materials for preparing the block B include aliphatic diisocyanate and aliphatic diamine; The molar ratio of block A to block B is 1:(0.4-4); The glass transition temperature of the block copolymer is -20 to 160°C; The elastic modulus of the block copolymer is 500-4000 Mpa; The binder is applied to lithium-ion batteries; The lithium-ion battery comprises a battery pole piece and an electrolyte.

2. The battery binder according to claim 1, characterized in that: The molar ratio of block A to block B is 1:(1-2.5).

3. The battery binder according to claim 1, characterized in that: The molar percentage of aromatic diisocyanate in the raw materials for preparing the block A is 30-49 mol%.

4. The battery binder according to claim 1, characterized in that: The aromatic diisocyanate includes any one or a combination of at least two of 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, xylylene diisocyanate, dimethylbiphenyl diisocyanate, p-phenylene diisocyanate, 1,5-naphthalene diisocyanate or 3,3-dichlorobiphenyl-4,4-diisocyanate.

5. The battery binder according to claim 1, characterized in that: The molar percentage of the aromatic diamine in the raw material for preparing the block A is 51-70 mol%.

6. The battery binder according to claim 1, characterized in that: The aromatic diamine includes any one of p-phenylenediamine, m-phenylenediamine, 4,4'-diaminodiphenyl ether, 3,4'-diaminodiphenyl ether, 4,4'-diaminobenzophenone, 4,4'-diaminodiphenyl sulfone, 3,3'-diaminodiphenyl sulfone, 4,4'-diaminobiphenyl, 4,4'-diaminodiphenylmethane, 2,2-bis[4-(4-aminophenoxy)phenyl]propane, 2,2'-bis(trifluoromethyl)diaminobiphenyl or 5-amino-2-(4-aminophenyl)benzimidazole, or a combination of at least two thereof.

7. The battery binder according to claim 1, characterized in that: The block A is prepared by the following method, which comprises: reacting an aromatic diisocyanate and an aromatic diamine in a solvent to obtain the block A.

8. The battery binder according to claim 7, characterized in that: The solvent includes N-methylpyrrolidone.

9. The battery binder according to claim 7, characterized in that: The reaction time is 60 to 360 min.

10. The battery binder according to claim 7, characterized in that: The reaction temperature is 50-70°C.

11. The battery binder according to claim 7, characterized in that: The method specifically comprises the following steps: (A1) dissolving an aromatic diisocyanate in a solvent to obtain an aromatic diisocyanate solution; dissolving an aromatic diamine in a solvent to obtain an aromatic diamine solution; (A2) adding the aromatic diisocyanate solution obtained in step (A1) to the aromatic diamine solution obtained in step (A1) to react and obtain the block A.

12. The battery binder according to claim 11, characterized in that: The mass percentage of the aromatic diisocyanate in the aromatic diisocyanate solution in step (A1) is 10-40%.

13. The battery binder according to claim 11, characterized in that: The mass percentage of the aromatic diamine in the aromatic diamine solution of step (A1) is 10-40%.

14. The battery binder according to claim 11, characterized in that: The adding time of step (A2) is 30 to 120 min.

15. The battery binder according to claim 1, characterized in that: The molar percentage of aliphatic diisocyanate in the raw materials for preparing the block B is 51-70 mol%.

16. The battery binder according to claim 1, characterized in that: The aliphatic diisocyanate includes any one of hexamethylene diisocyanate, trimethylhexamethylene diisocyanate, isophorone diisocyanate, dicyclohexylmethane diisocyanate or lysine diisocyanate, or a combination of at least two thereof.

17. The battery binder according to claim 1, characterized in that: The molar percentage of the aliphatic diamine in the raw material for preparing the block B is 30-49 mol%.

18. The battery binder according to claim 1, characterized in that: The aliphatic diamine includes any one of aliphatic carbon chain diamine, ether diamine, double amino-terminated polyamide or double amino-terminated polybutadiene-acrylonitrile copolymer or a combination of at least two thereof.

19. The battery binder according to claim 18, characterized in that: The aliphatic carbon chain diamines include 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,11-undecanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,36-triacontanediamine, 2,5-dimethyl-1,6-hexanediamine, 2,4-dimethyl-1,6-hexanediamine, 3,3-dimethyl-1,6-hexanediamine, 2,2-dimethyl-1,6-hexanediamine, 2,2,4-trimethyl-1,6-hexanediamine, 2,4,4-trimethyl-1,6-hexanediamine, 2,4-diethyl-1,6-hexanediamine, 2,2-dimethyl-1,7 -heptanediamine, 2,3-dimethyl-1,7-heptanediamine, 2,4-dimethyl-1,7-heptanediamine, 2,5-dimethyl-1,7-heptanediamine, 2-methyl-1,8-octanediamine, 3-methyl-1,8-octanediamine, 4-methyl-1,8-octanediamine, 1,3-dimethyl-1,8-octanediamine, 1,4-dimethyl-1,8-octanediamine, 2,4-dimethyl-1,8-octanediamine, 3,4-dimethyl-1,8-octanediamine, 4,5-dimethyl-1,8-octanediamine, 2,2-dimethyl-1,8-octanediamine, 3,3-dimethyl-1,8-octanediamine, 4,4-dimethyl-1,8-octanediamine or 5-methyl-1,9-nonanediamine, or a combination of at least two thereof.

20. The battery binder according to claim 18, characterized in that The ether-based diamine includes any one of bis(2-aminoethyl) ether, 3,6-dioxa-1,8-octanediamine, 4,7-dioxa-1,10-decanediamine, 4,7-dioxa-2,9-decanediamine, 4,9-dioxa-1,12-dodecanediamine, 5,8-dioxa-3,10-dodecanediamine, 4,7,10-trioxa-1,13-tridecanediamine, bis(3-aminopropyl)polytetrahydrofuran or polyoxyalkylene diamine, or a combination of at least two thereof.

21. The battery binder according to claim 18, characterized in that: The double amino-terminated polyamide includes any one of double amino-terminated polyamide 6, double amino-terminated polyamide 11, double amino-terminated polyamide 12, double amino-terminated polyamide 66, double amino-terminated polyamide 610, double amino-terminated polyamide 612, double amino-terminated polyamide 1010, double amino-terminated polyamide 1011, double amino-terminated polyamide 1012, double amino-terminated polyamide 1013, double amino-terminated polyamide 1111, double amino-terminated polyamide 1112, double amino-terminated polyamide 1113, double amino-terminated polyamide 1212, double amino-terminated polyamide 1213, double amino-terminated polyamide 1313 or double amino-terminated polyamide 1414, or a combination of at least two of them.

22. The battery binder according to claim 1, characterized in that: The aliphatic diamine has more than 10 carbon atoms in its main chain.

23. The battery binder according to claim 1, characterized in that: The block B is prepared by the following method, which includes: reacting an aliphatic diisocyanate and an aliphatic diamine in a solvent to obtain the block B.

24. The battery binder according to claim 23, characterized in that The solvent includes N -Methylpyrrolidone.

25. The battery binder according to claim 23, characterized in that: The reaction time is 60 to 360 minutes.

26. The battery binder according to claim 23, characterized in that: The reaction temperature is 50-70°C.

27. The battery binder according to claim 23, characterized in that: The method specifically comprises the following steps: (B1) dissolving an aliphatic diisocyanate in a solvent to obtain an aliphatic diisocyanate solution; dissolving an aliphatic diamine in a solvent to obtain an aliphatic diamine solution; (B2) adding the aliphatic diisocyanate solution obtained in step (B1) to the aliphatic diamine solution obtained in step (B1) to react and obtain the block B.

28. The battery binder according to claim 27, characterized in that: The mass percentage of the aliphatic diisocyanate in the aliphatic diisocyanate solution in step (B1) is 10-40%.

29. The battery binder according to claim 27, characterized in that: The mass percentage of the aliphatic diamine in the aliphatic diamine solution in step (B1) is 10-40%.

30. The battery binder according to claim 27, characterized in that The adding time of step (B2) is 30 to 60 min.

31. The battery binder according to claim 1, characterized in that: The viscosity of the block copolymer is 100-100000 mPa·s.

32. The battery binder according to claim 31, characterized in that The viscosity of the block copolymer is 1000-10000 mPa·s.

33. The battery binder according to claim 1, characterized in that: The glass transition temperature of the block copolymer is 40-120°C.

34. The battery binder according to claim 1, characterized in that: The elastic modulus of the block copolymer is 800-3000 MPa.

35. The battery binder according to claim 34, characterized in that The elastic modulus of the block copolymer is 1200-2500 MPa.

36. The battery binder according to claim 1, characterized in that The battery binder also includes a binder and / or a conductive material.

37. The battery binder according to claim 36, characterized in that Based on 100 parts by weight of the total weight of the battery binder, the content of the binder is 1 to 49 parts by weight.

38. The battery binder according to claim 36, characterized in that The bonding material includes any one of polyvinylidene fluoride, polytetrafluoroethylene, polyvinylidene fluoride copolymer, polytetrafluoroethylene copolymer, polyimide, polyetherimide, polyamideimide, polyesterimide, polycarbonateimide, polyureaimide, styrene-butadiene rubber, polyacrylonitrile, polyacrylic acid, polyacrylate, polyacrylic acid-polyacrylonitrile copolymer or polyacrylate-polyacrylonitrile copolymer, or a combination of at least two thereof.

39. The battery binder according to claim 38, characterized in that The bonding material includes any one of polyvinylidene fluoride, polyimide, polyamide-imide, polyacrylic acid or styrene-butadiene rubber, or a combination of at least two thereof.

40. The battery binder according to claim 36, characterized in that Based on 100 parts by weight of the total weight of the battery binder, the content of the conductive material is 1 to 49 parts by weight.

41. The battery binder according to claim 36, characterized in that The conductive material includes any one of conductive carbon black, conductive graphite, modified conductive graphite, metal particles, Ketjen black, carbon nanotubes, carbon fibers, graphene or conductive polymers, or a combination of at least two thereof.

42. A method for preparing a battery binder as claimed in any one of claims 1 to 41, characterized in that: The preparation method comprises the following steps: (1) mixing block A and block B, reacting to obtain an intermediate product; (2) Adding a chain extender to the intermediate product obtained in step (1) to carry out a reaction, and then adding a capping agent to carry out a reaction to obtain the battery binder.

43. The method for preparing a battery binder according to claim 42, characterized in that: The mixing in step (1) is carried out by adding block A to block B.

44. The method for preparing a battery binder according to claim 42, characterized in that: The adding time is 60 to 360 min.

45. The method for preparing a battery binder according to claim 42, characterized in that: The reaction time of step (1) is 60 to 360 min.

46. ​​The method for preparing a battery binder according to claim 42, characterized in that: The reaction temperature in step (1) is 60-90°C.

47. The method for preparing a battery binder according to claim 42, characterized in that: The amount of the chain extender added in step (2) is 0.2-2% of the total mass of block A and block B.

48. The method for preparing a battery binder according to claim 42, characterized in that: The chain extender in step (2) is an aliphatic diamine.

49. The method for preparing a battery binder according to claim 42, characterized in that: The temperature for reacting the chain extender in step (2) is 60-90°C.

50. The method for preparing a battery binder according to claim 42, characterized in that: The reaction time of adding the chain extender in step (2) is 30 to 120 minutes.

51. The method for preparing a battery binder according to claim 42, characterized in that: The amount of the end-capping agent added in step (2) is 0.1-1% of the total mass of block A and block B.

52. The method for preparing a battery binder according to claim 42, characterized in that: The end-capping agent in step (2) includes any one of methylamine, ethylamine, propylamine, dimethylamine, diethylamine, aniline, diphenylamine or p-aminobenzoic acid, or a combination of at least two thereof.

53. The method for preparing a battery binder according to claim 42, characterized in that: The reaction time of adding the end-capping agent in step (2) is 30 to 120 minutes.

54. The method for preparing a battery binder according to claim 42, characterized in that: The temperature for reacting the end-capping agent in step (2) is 20-40°C.

55. The method for preparing a battery binder according to claim 42, characterized in that: Step (2) also includes adding N- Methylpyrrolidone was used for the dilution step.

56. A battery pole piece, characterized in that: The battery electrode comprises the battery adhesive as described in any one of claims 1 to 41.

57. The battery pole piece according to claim 56, characterized in that: The battery electrode is a positive electrode or a negative electrode.

58. A lithium ion battery, characterized in that: The lithium-ion battery comprises the battery pole piece as described in claim 56 or 57.

Citation Information

Patent Citations

  • Adhesive and lithium ion battery with same

    CN105514488A

  • Binder for high-nickel ternary material positive plate, positive plate and battery

    CN112186189A

  • Polyamide-imide binder for lithium ion battery and electrode plate

    CN113571704A

  • Mussel biomimetic polymer and preparation method thereof, positive electrode binder and secondary battery

    CN113773419A

  • Solid electrolyte composition, binder for all-solid-state secondary batteries, and electrode sheet for batteries and all-solid-state secondary battery each using said solid electrolyte composition

    CN105580186A